2017
DOI: 10.1140/epjds/s13688-017-0110-z
|View full text |Cite|
|
Sign up to set email alerts
|

Instagram photos reveal predictive markers of depression

Abstract: Using Instagram data from 166 individuals, we applied machine learning tools to successfully identify markers of depression. Statistical features were computationally extracted from 43,950 participant Instagram photos, using color analysis, metadata components, and algorithmic face detection. Resulting models outperformed general practitioners' average unassisted diagnostic success rate for depression. These results held even when the analysis was restricted to posts made before depressed individuals were firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
258
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(273 citation statements)
references
References 43 publications
9
258
0
6
Order By: Relevance
“…For example, most users on Twitter were classified as emotionally stable and extroverted by using counts of the Twitter information 'following', 'followers', and 'listed' [28]. Additionally, Reece and Danforth [29] successfully identified markers of depression from participants' Instagram photos, which surpassed general practitioners' typical unassisted diagnostic success rate for depression. Quercia, et al [30] evaluated the efficacy of digital methods to predict the strength of online social relationships on Facebook and their findings were consistent with previous analyses used on Twitter [31].…”
Section: Social Media Data In Psychology Researchmentioning
confidence: 99%
“…For example, most users on Twitter were classified as emotionally stable and extroverted by using counts of the Twitter information 'following', 'followers', and 'listed' [28]. Additionally, Reece and Danforth [29] successfully identified markers of depression from participants' Instagram photos, which surpassed general practitioners' typical unassisted diagnostic success rate for depression. Quercia, et al [30] evaluated the efficacy of digital methods to predict the strength of online social relationships on Facebook and their findings were consistent with previous analyses used on Twitter [31].…”
Section: Social Media Data In Psychology Researchmentioning
confidence: 99%
“…Much of the previous research has largely been focused on understanding a user's mental well-being through information that the user posts on social media, such as Twitter "Tweets", Facebook status updates, or Instagram images [10][11][12]17]. Other studies, however, have suggested that community-generated data is correlated with user-generated data, as alcohol-related posts have more positive community-generated data [24].…”
Section: Using Community-generated Data Improves Detection Of Depressionmentioning
confidence: 99%
“…Prediction of MDD based on social media data is well established with strong results [10,11,17,22,28]. However, the existing literature has largely focused on using only user-generated data for this purpose.…”
Section: Comparison To Previous Workmentioning
confidence: 99%
See 2 more Smart Citations